Энциклопедия этикета - Панкеев Иван Алексеевич (ОЛМА-ПРЕСС, 2001)
На обл. авт. не указан Экземпляры: ЧЗ (20160121) / Инвентарный номер: 36045 / Цена: 90.00 / Сис.шифр: 87.7 / Авт.знак: П 16 / ГРНТИ: 02 / ББК: 87.774